Resonance Fatigue Behaviour of Concretes with Recycled Cement and Aggregate - Cantero, Blas (2021)
The huge increase in production of construction and demolition waste (CDW) worldwide is leading to the valorisation of as recycled aggregates. One of the most promising alternatives is its use as a recycled aggregate in the manufacture of structural concrete, which motivates the study of the dynamic behaviour of these materials in order to ensure their suitability for use in elements subjected to dynamic loads. This work evaluated the resonant compressive fatigue behaviour of structural concretes with 25% or 50% recycled mixed aggregates, either individually or in combination with 25% recycled cement of clay-based materials both from CDW. All mixes were subjected to compressive fatigue tests using the accelerated Locati method. Regarding the fatigue limit, the results showed that for all mixes, it was between 30% and 45% of the compressive strength. In addition, a correlation was also found between the resonance frequency of the test and the deformation suffered by the specimen. This correlation enabled the estimation of the fatigue limit through a more stable parameter than the strain measured by strain gauges, namely, the resonance frequency. In addition, it was found that the resonance frequency of the test changed as the specimen damage increased. This observation enabled the estimation of the fatigue limit through a more stable parameter than the strain measured by strain gauges, namely, the resonance frequency.